Mathematical Reasoning Based on Gender: Mapping The Literature By Bibliometric Analysis - Afifah, A; Maarif, samsul (IndoMath: Indonesia Mathematics Education, 2022)
This study aims to analyze the literature review based on the analytic database on google scholar about mathematical reasoning related to gender. A total of 200 papers on mathematical reasoning were published in the harzing data base from 1959 to 2021 and analyzed through a bibliometric analysis approach. Aggregation of bibliographies from sources, authors, countries, institutions, publications and co-occurrence of authors' keywords were analyzed and visualized through VOSViewer software. Mathematical reasoning is heavily influenced by other things, one of which is related to gender differences in it. The results from the bibliometric data of the Harzing Application and VOSViewer that there is a distribution related to mathematical reasoning is very closely related to the key words difference, mathematical reasoning ability, reasoning, reasoning ability, mathematical ability, boy, girl, female, and male. The journal that has a lot of research on mathematical reasoning based on gender is the Journal of Educational Psychology, an institution that researches a lot on mathematical reasoning based on gender is the American Psychological Association. And the country that has researched the most on mathematical reasoning is the United States.